Commodification of the Elderly in TikTok Live Streaming (TikTok Account Case Study @intan_komalasari92) - Irvan Manggala; Ismi Dwi Astuti Nurhaeni; Andre Rahmanto (Formosa Journal of Social Sciences (FJSS), 2023)
TikTok is a social media platform that facilitates live broadcasts that benefit from monetary rewards for content creators. This study aims to analyze the exploitation of older adults in TikTok live streaming, using phenomenological methods with a qualitative descriptive approach. The results show older adults to be talents who beg online in TikTok live streaming content. Driving factors include a desire for attention and income, supported by accessible internet and social media access that broadens the narrative. Social media provides an excellent opportunity for online beggars to attract netizens' attention through sensations and complaining activities due to boredom on social media. The empathy of netizens is the driver of viral online begging content by utilizing the saweran feature. The negative impacts include violating legal norms, undermining human values, and creating unhealthy economic and financial dependence on online begging practices through TikTok live streaming